2022
DOI: 10.1007/s10336-021-01946-1
|View full text |Cite
|
Sign up to set email alerts
|

The European Turtle Dove in the ecotone between woodland and farmland: multi-scale habitat associations and implications for the design of management interventions

Abstract: The European Turtle Dove (turtle dove) is globally threatened after undergoing a sustained and generalised decline across its breeding range, with habitat loss suggested as the main driver. Here, we reviewed the scientific literature on habitat associations across its European breeding range, in relation to distribution, breeding numbers, nesting substrates, food and foraging habitats, to identify optimal habitat management measures. Large-scale distribution seemed related to the availability, but not dominanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…The sustainability of the species hunting in Europe is discussed during the last several years due to a decline in its population [8][9][10]. In 2018, the European Commission approved the International Species Action Plan [2], which suggested a temporary hunting moratorium.…”
Section: Introductionmentioning
confidence: 99%
“…The sustainability of the species hunting in Europe is discussed during the last several years due to a decline in its population [8][9][10]. In 2018, the European Commission approved the International Species Action Plan [2], which suggested a temporary hunting moratorium.…”
Section: Introductionmentioning
confidence: 99%
“…Most nest‐site characteristics (habitat, height and tree species) contrasted with those reported by previous studies carried out in patchy farmland landscapes and where most nests were found in shrubs, hedgerows or small woodland patches (see Carboneras et al . 2022 for a review). Among tree species used for nesting, maples, oaks and European Beech dominated (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Values from Portugal reported by Dias (2016) ranged from 1.68 to 2.14, and in Britain, Browne and Aebischer (2004) reported 1.3 young per pair in 1998-2000, and Murton (1968) reported 2.1 in the 1960s (1960-62, 1966. In their recent review, Carboneras et al (2022) suggest that early in the season young birds will depend more on wild seeds than cultivated seeds, yet our results do not suggest that birds were food limited during this period, as numerous nests (n = 22) were found in May. However, we cannot rule out the possibility that our network of traps continuously baited from mid-April to late June may have provided European Turtle Doves with supplementary food, enabling them to initiate and raise broods early in the season and/or to renest shortly after their first attempt (but see Browne & Aebischer 2002and Dunn et al 2021in Carboneras et al 2022.…”
Section: Breeding Success and Productivitymentioning
confidence: 99%
“…Most studies on both European and Northwest African subspecies of Turtle Doves have focused on farmland habitats, involving reproductive biology [14,34,35], breeding habitat use [8,30,34,41,46], foraging habitat selection [15,[38][39][40], and migration [1,8,41,46]. However, in forests, studies were limited to habitat use [46,[47][48][49] and feeding resources [41,46]. Tese studies revealed variable results concerning breeding performances and clarifed the main threatening factors [9,31].…”
Section: Introductionmentioning
confidence: 99%
“…Tese studies have detailed breeding biology, reproductive success, and menacing factors. However, the selection of nesting trees inside breeding orchards was neglected in Europe [41,48] and North Africa [9,30,47,49]. Tis element is of great importance in clarifying patterns of nesting site selection with regards to orchard characteristics, tree heights, and disturbing factors [49].…”
Section: Introductionmentioning
confidence: 99%